Guide for community leaders to meet the challenges of personal preparation in the event of a disaster. (5th August 2021) - Ingham, Valerie; Islam, Mir Rabiul; Hicks, John; Burmeister, Oliver
Abstract: Objective: In the aftermath of fires which swept through a regional community in 2013, community leaders were thrust, unprepared, into the disaster recovery arena. The objective of this research was to investigate the subsequent lived experience of these community leaders and, based on this information, develop a guide to meet the challenges for their personal preparation in the context of disaster. Design: Ethical approval for the overarching Community Connections project was provided by Charles Sturt University (H2014073). The project design was informed by an interpretivist paradigm and the methodology embraced participatory action research and thus engaged community members and leaders as research partners. This paper reports on the community leader component of the overarching project. Setting: Blue Mountains, New South Wales, Australia. Participants: There were 7 interview participants in both 2014 and 2018; 5 participated in both years. Participants were either managers of a local non‐government organisation, peak body, school, emergency service or large relief organisation with a local presence. Main outcome measure: The development of a guide for the personal preparation of community leaders. Results: The stress of community leaders escalated after the disaster, resulting in a debilitating blurring of professional and personal boundaries, heightened demand on personal knowledge, networking relationships and communication strategies. Conclusion: The guide is practical and far reaching; the researchers could not locate anything similar to guide community leaders in their personal planning and preparation for work in disaster recovery.